2010
DOI: 10.1080/09658211003601548
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sleep on episodic memory in older and younger adults

Abstract: Evidence on sleep-dependent benefits for episodic memory remains elusive. Furthermore we know little about age-related changes on the effects of sleep on episodic memory. The study we report is the first to compare the effects of sleep on episodic memories in younger and older adults. Memories of stories and personal events were assessed following a retention interval that included sleep and following an equal duration of wakefulness. Both older and younger adults have superior memory following sleep compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 16 publications
10
85
4
1
Order By: Relevance
“…Overall, these data strongly suggest that the age-related deficits in declarative memory consolidation during sleep are due to a decline in SWS. In line with these findings, in aged individuals (69 -80 years), the improvement in the recollection of hippocampus-dependent episodic memories (for personally experienced events) after retention periods of nocturnal sleep, with reference to recollection after daytime wakefulness, was less pronounced than in young (19 -29 years) subjects (21). A recent study reported no beneficial effect of sleep on memory and no correlation between SWS and consolidation of word pairs across sleep in elderly subjects (60 -84 years), whereas a positive correlation with SWS and a sleep-dependent memory improvement was observed in younger participants (18 -22 years) (1055) A diminished capability to consolidate hippocampus-dependent memory (for word pairs) was not confirmed in a recent study by Wilson et al (1324) including, besides young subjects, middle-aged (30 -55 years) as well as old (55-70 years) participants.…”
Section: Hippocampus-dependent Declarative Memorysupporting
confidence: 77%
“…Overall, these data strongly suggest that the age-related deficits in declarative memory consolidation during sleep are due to a decline in SWS. In line with these findings, in aged individuals (69 -80 years), the improvement in the recollection of hippocampus-dependent episodic memories (for personally experienced events) after retention periods of nocturnal sleep, with reference to recollection after daytime wakefulness, was less pronounced than in young (19 -29 years) subjects (21). A recent study reported no beneficial effect of sleep on memory and no correlation between SWS and consolidation of word pairs across sleep in elderly subjects (60 -84 years), whereas a positive correlation with SWS and a sleep-dependent memory improvement was observed in younger participants (18 -22 years) (1055) A diminished capability to consolidate hippocampus-dependent memory (for word pairs) was not confirmed in a recent study by Wilson et al (1324) including, besides young subjects, middle-aged (30 -55 years) as well as old (55-70 years) participants.…”
Section: Hippocampus-dependent Declarative Memorysupporting
confidence: 77%
“…For comparison, grammatical reasoning decreased slightly between the first half and the second half of the night in the sleep deprivation study, indicating that practice alone was not enough to improve performance independent of sleep. These results suggest that the sleep episode in the non-sleep deprivation study may have contributed to an improvement in grammatical reasoning performance, supporting previous studies indicating that sleep plays an active role in improving performance and memory (Aly & Moscovitch, 2010;Lau, Tucker, & Fishbein, 2010;Rasch & Born, 2008). Future research could be designed to examine why performance on only the grammatical reasoning task improved under non-sleep deprivation conditions.…”
Section: Apts Performancesupporting
confidence: 62%
“…Although old mice tend to have reductions in sleep compared with young mice, they still obtain substantial amounts of sleep, whereas gentle handling SD has been shown to be highly effective at eliminating all sleep during the SD period (Hasan et al 2012). Consistent with this view, a study in humans found that episodic memory in both young and old subjects was better preserved across a period of sleep than a period of wakefulness, demonstrating that the sleep older people obtain is still beneficial for memory (Aly and Moscovitch 2010). One might have expected that young mice, presumably achieving greater amounts of more consolidated sleep than aged mice, would have demonstrated better initial memory consolidation, but they did not, either in terms of total freezing or the specificity of memory for the trained context.…”
Section: Sleep Deprivation In Aged Animals Causes Memory Impairments supporting
confidence: 59%